The Use of Topical Lidocaine Gel During Intermaxillary Fixation Procedure. Issue 5 (July 2016) - Jeong, Yeon Jin; Kim, Ho Jun; Kwon, Ho; Shim, Hyung-sup; Seo, Bommie Florence; Jung, Sung-No
Abstract : Abstract: This study aimed to validate the usefulness of lidocaine gel during intermaxillary fixation using arch bars in patients with mandible fracture by comparing 2 patient groups: one group using lidocaine gel in intermaxillary fixation and the other group undergoing traditional local infiltration. Subjects were patients with mandible fracture undergoing intermaxillary fixation using arch bars from March 2003 to February 2007. Twenty-three patients were anesthetized in the upper and lower gingiva by 2% local lidocaine solution injection; another 23 underwent topical anesthesia with 2% lidocaine hydrochloride gel applied to the upper and lower gingiva. The convenience of fixation was measured in terms of operation time and degree of pain according to the visual analog scale; arch bar loosening rate was assessed postoperatively. The mean operation times were 63 and 47 minutes in the groups undergoing local infiltration and using topical lidocaine gel, respectively. For pain degree according to the visual analog scale, the mean scores were 6.4 and 3.2 in the groups using local infiltration and topical lidocaine gel, respectively. When the arch bar loosening rate was measured postoperatively, the 2 groups differed significantly, with a rate of 26% in the group using local infiltration and 13% in the group using topical lidocaine gel. Application of topical lidocaine gel during intermaxillary fixation using arch bars in patients with mandible fracture relieves pain and offers convenience in performing the procedure. It can be a useful alternative method for patients who are sensitive to pain or have needle phobia.